2013
DOI: 10.1021/pr400697s
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in Deciphering the Auxin Commitment in the Arabidopsis thaliana Root Growth

Abstract: The development of plant root systems is characterized by a high plasticity, made possible by the continual propagation of new meristems. Root architecture is fundamental for overall plant growth, abiotic stress resistance, nutrient uptake, and response to environmental changes. Understanding the function of genes and proteins that control root architecture and stress resistance will contribute to the development of more sustainable systems of intensified crop production. To meet these challenges, proteomics p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…Initial characterization of auxin-responsive proteomes in seedlings and roots identified proteins that are responsive 6–24 h after auxin treatment (10, 11) and protein phosphorylation events associated with auxin-mediated lateral root formation (12). However, further studies of the auxin-regulated proteome are needed to generate a more comprehensive view of auxin-mediated gene expression (13).…”
mentioning
confidence: 99%
“…Initial characterization of auxin-responsive proteomes in seedlings and roots identified proteins that are responsive 6–24 h after auxin treatment (10, 11) and protein phosphorylation events associated with auxin-mediated lateral root formation (12). However, further studies of the auxin-regulated proteome are needed to generate a more comprehensive view of auxin-mediated gene expression (13).…”
mentioning
confidence: 99%
“…Additionally, transcriptional changes in Arabidopsis seedlings have been well documented . Initial characterization of auxin responsive proteomes in seedlings and roots identified proteins that are responsive 6–24 h after auxin treatment, but further studies of the auxin‐regulated proteome are needed to generate a more comprehensive view of auxin mediated gene expression …”
mentioning
confidence: 99%
“…[3][4][5][7][8][9][10] Initial characterization of auxin responsive proteomes in seedlings and roots identified proteins that are responsive 6-24 h after auxin treatment, [11][12][13] but further studies of the auxin-regulated proteome are needed to generate a more comprehensive view of auxin mediated gene expression. [14] In this study, we characterized the auxin-regulated proteome in Arabidopsis by treating 5-day-old seedlings grown on 0.5× Murashige and Skoog (MS) media overlaid with nylon mesh with 1 µm indole-3-acetic acid (IAA), a naturally occurring auxin ("auxin treated"), or an equivalent volume of 95% ethanol diluted in 0.5× MS ("mock" treated) for 3 h (Figure 1A). Proteins were extracted and processed into peptides, which were iTRAQ 4-plex labeled, pooled, and then identified and quantified using tandem mass spectrometry (MS/MS) ( Figure 1A) according to previously utilized methods.…”
mentioning
confidence: 99%
“…The effects of auxin on Arabidopsis root growth at the protein level has been reviewed [ 5 ]. Zhang et al [ 6 ] observed changes in the phosphorylation status of 20 proteins, including SORTING NEXIN 1 (SNX1), after exposure of roots to auxin for 2 h. The additional mutational analysis of serine 16 of SNX1 demonstrated its involvement in lateral root formation.…”
Section: Introductionmentioning
confidence: 99%